Persepsi Pemustaka yang Menggunakan Media Sosial (Facebook dan Twitter) Terhadap Peningkatan Layanan Informasi Badan Perpustakaan dan Kearsipan Provinsi Sumatera Barat - Jalinur, Jalinur; Nelisa, Malta (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2015)
The purpose of writing this article for description. 1) to describe the function of social media which use the librarian.Â 2) to describe perception about library information in social media. Analysis of this data take by describtion can be concluded. 1) there are many social media function to share the information and entertainment. 2) librarian perception about sprate of information in social media, give positif respons, it means can be search information, how to be important the true information and social media for librarian and how to be important the librarian get information. Keywords: perseptio; social media; information